Haemangiosarcoma of breast. Issue 6 (September 1971) - Kessler, E.; Kozenitzky, I. L.
Abstract : This is a report of a haemangiosarcoma involving the breast, spleen, liver, lungs, and subcutaneous tissue. There appears to be evidence that the tumour arose in the breast with the other sites representing metastases rather than a malignant transformation of multiple haemangiomatoses. Histologically the primary breast tumour appeared deceptively innocuous.